The middle years slump: addressing student-reported barriers to academic progress. Issue 6 (19th September 2018) - Jevons, Colin; Lindsay, Sophie
ABSTRACT: First-year university student attrition has been widely explored. However, there is a gap in our understanding when it comes to later years. Why do students who successfully navigate the hurdles of transition into university become at risk of exclusion in the middle years of study because of poor academic progress? This qualitative project develops a student-centred understanding of the problem of attrition through academic failure. It investigates the reasons given by students wishing to avoid involuntary exclusion from their course. Specifically, we address why middle-year students say they fail when they wish to succeed by examining self-reports. We find six main self-reported themes in three categories. The problems faced by mid-degree undergraduates are broader and more complex than those encountered in the first year. Our findings contrast with previous work on first-year attrition, which found that negative expectations of their own ability to succeed were a major factor in students' decisions to drop out, although our study is constructed differently in that we analyse people wishing to continue their studies. The results expand our understanding of student involuntary attrition in the middle years. The overarching major issues in the themes we identified were financial, family/personal issues and health problems. In particular, mental health issues were remarkably apparent. This has significant implications for future student support. We find that there are commonly multiple reasons underlying each student's at-risk status and provide suggestions for managers of programs that help students succeed.